2015
DOI: 10.1038/srep10687
|View full text |Cite
|
Sign up to set email alerts
|

Efficient delivery of antigen to DCs using yeast-derived microparticles

Abstract: Some pathogens can be naturally recognized and internalized by antigen presentation cells (APCs) in vivo, providing a platform for efficient vaccine delivery. However, the biosafety concerns discourage the clinical applications of live pathogens. Here, yeast-derived microparticles were prepared for cancer vaccine delivery. By chemical treatment of bread yeast, capsular yeast shell (YS) microparticles were obtained. Ovalbumin (OVA), as a model antigen, was conjugated to the surface of YS. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
(41 reference statements)
2
29
0
Order By: Relevance
“…Dietary supplementation with β-glucans can modulate immune function and protect against pathogen infections [ 30 , 37 , 38 ]. Similarly, recent study demonstrated that yeast-derived microparticles (mainly cell walls) induced effective immune response against tumor cells in vivo , thus stimulating both humoral and cellular immunity [ 39 ]. Consistent with that, SFY used here was more effective than HKY in immunostimulation, possibly due to its smaller particle size of cell wall components in yeasts increasing the rate and extent of absorption or interaction with the enterocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with β-glucans can modulate immune function and protect against pathogen infections [ 30 , 37 , 38 ]. Similarly, recent study demonstrated that yeast-derived microparticles (mainly cell walls) induced effective immune response against tumor cells in vivo , thus stimulating both humoral and cellular immunity [ 39 ]. Consistent with that, SFY used here was more effective than HKY in immunostimulation, possibly due to its smaller particle size of cell wall components in yeasts increasing the rate and extent of absorption or interaction with the enterocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Capsular yeast shell microparticles were used to deliver OVA to dendritic cells. The particles are well recognized by dendritic cells and, upon internalization, trigger release of co‐stimulatory molecules . Figure and Figure show robust stimulation of humoral and cellular immune responses resulting from vaccination with antigen‐loaded glucan particles.…”
Section: Glucan‐based Drug and Vaccine Deliverymentioning
confidence: 93%
“…One of the first examples of a supported microscale liposome was by Lee and co‐workers over two decades ago, where the authors developed a so‐called lipobead with a hydrogel as its core material . More recently, Gou and co‐workers 2–4 µm microcapsules made from yeast cells to display antigenic OVA for effective delivery to dendritic cells . To manufacture uniformly sized microscale liposomes, Deshpande and Dekker developed a high‐throughput technique to make monodisperse microscale liposomes of tunable size using microfluidics …”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%